Successes & Failures in EU Cohesion Policy: An Introduction to EU cohesion policy in Eastern, Central, and Southern Europe - Idczak, Piotr (De Gruyter, 2020)
The book offers though-provoking insights on the performance and effectiveness of EU cohesion policy in Eastern, Central, and Southern Europe by highlighting the key achievement and identifying the main shortcomings. One of the most important advantages of the book is that it covers many distinct actions of this policy, the authors also, based on wide-ranging analysis, formulate policy recommendations for the future.